IDENTIFYING STUDENTS’ LEVEL OF PSYCHOLOGICAL WELL-BEING AMIDST THE COVID-19 PANDEMIC - Акишева, Айслу; Ауэзова, Амина (Pedagogy and Psychology, 2022)
The article examines the level of psychological well-being of students during the COVID-19 pandemic. The aim of the empirical psychological study was to conduct a comparative analysis of the psychological state of Kazakh and Bulgarian students during the COVID-19 pandemic, to identify the influence of cultural differences on the results obtained on the negative attitude and fears of students.A survey was conducted on the Google Forms platform, which was attended by 140 students of the L.N.Gumilev Eurasian National University (Nur-Sultan, Kazakhstan) and 92 students of the N.Vaptsarov Naval Academy (Varna, Bulgaria). It was revealed that the mood of respondents directly depends on the level of their optimistic or pessimistic mood. Those who define their mental state as good, stable, have higher values of optimism, as well as lower values of negative expectations.The results of the study indicate a direct relationship between the respondents’ responses and their psychological state, which were directly affected by events related to the COVID-19 pandemic, primarily the period of forced social isolation. In general, both Kazakh and Bulgarian students are optimistic, they are balanced and positive. The conducted research showed that despite a fairly high positive indicator of stress resistance of Kazakhstani students, indicators of negative expectations such as fear, anxiety, fatigue, depression, loneliness, burnout were revealed. These students should not be ignored, they should be provided with psychological support.